2000
DOI: 10.1007/s100960050483
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bacterial Virulence Factors and Host Factors in the Outcome of Escherichia coli Bacteraemia

Abstract: In a study of the role of virulence factors in the outcome of Escherichia coli bacteraemia, blood isolates from 30 hospitalised patients were characterised with regard to O and K antigens, P and type 1 fimbriae, haemolysin production, cytonecrotising factor 1 production, serum resistance, ability to activate neutrophils and resistance to killing. Patients were analysed to identify host factors contributing to morbidity and mortality. In univariate analyses the presence of a K antigen, type 1 fimbriae, absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
3
16
3
Order By: Relevance
“…Present data suggest that the source of infection and host factors, rather than the inferred amount of virulence traits, are the major determinants of prognosis of E. coli bacteremia. This observation agrees with the data from a previous study, in which patients with hemolysin-producing strains in fact had a better prognosis (11). Evidence that high-degree bacteremia as defined in this study was associated with some sources and had prognostic significance may have practical consequences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Present data suggest that the source of infection and host factors, rather than the inferred amount of virulence traits, are the major determinants of prognosis of E. coli bacteremia. This observation agrees with the data from a previous study, in which patients with hemolysin-producing strains in fact had a better prognosis (11). Evidence that high-degree bacteremia as defined in this study was associated with some sources and had prognostic significance may have practical consequences.…”
Section: Discussionsupporting
confidence: 92%
“…The genetic elements encoding these factors have been concentrated predominantly in strains derived from phylogroup B2 and, to a lesser extent, from group D, whereas isolates of groups A and B1 usually contain few virulence determinants and are essentially regarded as commensals (8,14,25,26). Although certain virulence factors have been associated with invasion of specific organs and shedding into the bloodstream (14,22,28), there is no proof that they have any impact on prognosis of patients with bacteremia (11). As a matter of fact, mortality associated with bloodstream E. coli infections seems to be influenced mostly by host and treatment factors (10,21,27), and patients with local or general compromising conditions are less frequently infected by highly virulent strains (25).…”
mentioning
confidence: 99%
“…It should be noted that this type P fimbriae is associated to strains belonging to phylogenetic group A. It has been previously demonstrated that fimbriae are important in the early stages of UTI and could be involved in the evolution towards bacteraemia, although low virulence strains can also cause severe disease, mainly among patients with risk factors, suggesting a complex interaction between virulence and host factors [31,32].…”
Section: Discussionmentioning
confidence: 97%
“…Relatively few studies have jointly examined the roles of host and bacterial factors in the severity and outcome of this infection (14, 17, 25, 30-32, 36, 50). The discrepancies among the conclusions of those studies might reflect the retrospective (14,31,36,50) and/or monocenter (14,30,32,36,50) nature of most of them, the small number (30 to 185) of patients included (14, 17, 30-32, 36, 50), the small number of bacterial factors examined (14, 17, 25, 30-32, 36, 50), and the diversity of the disease's pathophysiological mechanisms.…”
mentioning
confidence: 99%